2001
DOI: 10.1007/s11325-001-0013-9
|View full text |Cite
|
Sign up to set email alerts
|

Improving Compliance with Nasal CPAP and Vigilance in Older Adults with OSAHS

Abstract: The present study examined the efficacy of a cognitive-behavioral intervention at improving compliance with CPAP and vigilance in older adults with obstructive sleep apnea/hypopnea syndrome (OSAHS). Participants included 12 subjects who were randomized into one of two groups controlling for age, education, disease severity, and vigilance. The experimental group received two 45-min sessions designed to educate subjects on the consequences of OSAHS and the efficacy of CPAP. The control group received the same ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(22 citation statements)
references
References 20 publications
2
20
0
Order By: Relevance
“…(7173) The earliest study to examine a CBT intervention was a pilot randomized placebo-controlled trial in older adults (age 63.4 ± 4.5 years) with severe OSA, naïve to CPAP. (73) The intervention group received 2–45 minute sessions, one-on-one, that provided participant-specific information about OSA, symptoms, cognitive testing performance, treatment relevance, goal development, changes in symptoms with CPAP, troubleshooting advice, treatment expectations, and treatment goal refinement. There were no differences in short-term CPAP use (i.e., 1 and 4 weeks).…”
Section: What Interventions Promote Cpap Adherence?mentioning
confidence: 99%
“…(7173) The earliest study to examine a CBT intervention was a pilot randomized placebo-controlled trial in older adults (age 63.4 ± 4.5 years) with severe OSA, naïve to CPAP. (73) The intervention group received 2–45 minute sessions, one-on-one, that provided participant-specific information about OSA, symptoms, cognitive testing performance, treatment relevance, goal development, changes in symptoms with CPAP, troubleshooting advice, treatment expectations, and treatment goal refinement. There were no differences in short-term CPAP use (i.e., 1 and 4 weeks).…”
Section: What Interventions Promote Cpap Adherence?mentioning
confidence: 99%
“…The positive effects may be difficult to sustain when intensive support stops. Motivational enhancement therapy 6668 and cognitive behavioral therapy 69 are promising interventions based on either self-management of disease or motivational enhancement, and have been reported to improve CPAP adherence. Self-efficacy and social support are important elements in these successful interventions.…”
Section: Introductionmentioning
confidence: 99%
“…99 In a recent review of interpersonal factors in insomnia, Rogojanski and colleagues 100 presented a model for integrating bed partners into cognitive behavioral therapy to further enhance its efficacy. This model offers great insight into how to integrate spouses into behavioral interventions such as cognitive behavioral therapy 69 and motivational enhancement therapy 66, 67 to improve their effectiveness at increasing CPAP adherence.…”
Section: Introductionmentioning
confidence: 99%
“…Weaver et al showed a dose response on day time function on CPAP duration after 3 months of treatment by MSLT and questionnaire [35]. Aloie et al showed baseline neuropsychologic function have influence on the compliant rate and additional improvements in psychomotor speed and nonverbal learning was noted in compliant patients [36,37]. Active intervention could improve the compliance rate in their study.…”
Section: Discussionmentioning
confidence: 92%